(untitled) (Research, Society and Development, 2022)
Neoplasms in the elderly has been increasingly frequent and a number of factors may justify such a prognosis. Tumor sites vary greatly in addition to clinical manifestations. The objective of the present study is to intervene in the nutritional trajectory of the patient with colon cancer during the period in which she remained hospitalized. This is a case study in which a nutritional monitoring of a patient diagnosed with colon cancer was carried out. Female patient, 83 years old, weighing 63.44kg, classified as eutrophic based on her BMI: 28.19 kg/m. She was referred to the Hospital with complaints of urinary infection, frequent fevers, daily diarrhea, with the presence of blood. A diet with 2000.25 kcal hyperproteic, normoglycidic and normolipidic was prescribed. It was possible to observe a clinical and physiological improvement, leaving the post-surgical chronic constipation, evolving towards a better acceptance of the diet and avoiding a possible protein-energy malnutrition. Hemodynamically stable, but with some biochemical tests with alterations. Thus, the patient, even having performed the colectomy, must remain under periodic medical and nutritional follow-up. After discharge, her daughter received nutritional therapeutic guidelines, with the aim of improving her clinical condition even more. Thus contributing to a more effective comprehensive care for the patient, for being at home, as well as a better quality of life.